THE PREVALENCE OF CHRONIC KIDNEY DISEASE MARKERS IN ARTERIAL HYPERTENSION PATIENTS AND RELATION WITH DIABETES: RESULTS OF EPIDEMIOLOGICAL STUDY KHRONOGRAPH - Zh. D. Kobalava; S. V. Villevalde; N. Kh. agmanova; M. М. Batyushin; G. М. Orlova (Российский кардиологический журнал, 2018)
Aim. Under the framework of non-interventional observational multi-center program KHRONOGRAPH (Acquisition of additional data on the prevalence of declined glomerular filtration rate and albuminuria in systemic hypertension patients with and with no diabetes mellitus type 2 in Russian Federation) to evaluate the prevalence of chronic kidney disease (CKD) markers.Material and methods. In 1363 patients with arterial hypertension (AH) and/or type 2 diabetes (DM2) the glomerular filtration rate (GFR) was calculated with CKD-EPI, and albuminuria (AU) assessed via albumin/creatinine ratio (ACr) in morning urine.Results. In DM2 patients (n=779, 62,6% women, 63,8 y. o.) comparing to non-DM2 patients (n=584, 50,7% women, 60,5 y. o.) there was more common decrease of GFR <60 mL/min/1,73 m2 (38 and 31%), <45 mL/min/1,73 m2 (G3b-G5) (15,92 and 9,94%) and <30 mL/min/1,73 m2 (G4-G5) (4,24 and 2,06%), high and very high AU (36,6 and 28,1%), very high AU (А3) — (7,32 and 2,40%). In DM2 patients there was more common presence of at least one marker of CKD <60 mL/min/1,73 m2 and/or ACr >30 mg/g) (54,0 and 44,35%), isolated GFR decrease <60 mL/min/1,73 m2 (17,46 and 16,27%), isolated increase of ACr >30 mg/g (15,66 and 13,35%) and combination of decreased GFR and high/very high AU (20,93 and 14,71%). Among DM2 patients, the portion is lower of decreased combination risk of CKD progression and cardiovascular complications (45,2 and 53,6%), higher — in very high risk (28,5 and 20%). Most prevalent are the combinations related to early stages of CKD: G3аА1, G2А2 and G3аА2.Conclusion. In Russian Federation, patients with AH, regardless of DM2, are characterized by high rate of CKD markers. In DM2 patients comparing to those with none, there was more prevalent GFR decrease <60 mL/min/1,73 m2, increase of ACr >30 mg/g isolated and in combination. In AH and DM2 the portion of patients with a very high risk of CKD progression and cardiovascular complications is higher.